Method of Istinbath Al-Ahkam and Law Socialization by the Salafi-Wahabi Manhaj: Impacts on Social Interactions - Armaya Azmi; Faisar Ananda Arfa; Zainul Fuad; Syafaruddin Syafaruddin (Jurnal Madania)
This study examines the method of istinbath al-ahkam (deriving legal rulings) employed by scholars and leaders of the Salafi-Wahabi manhaj in issuing fatwas in North Sumatra and its impact on social interaction and harmony among different religious communities. The research adopts a combined approach, encompassing a doctrinal perspective on istinbath al-ahkam and a non-doctrinal view on legal socialization issues. Through literature review, interviews, and observations, data is gathered from the fatwas of Salafi-Wahabi scholars such as Sheikh Muhammad Nasiruddin Albani, Abdullah bin Baz, and Muhammad Shalih Fauzan. The findings indicate that the istibath al-ahkam method applied by Salafi-Wahabi adheres to the principles of the Ahlu Sunnah wal Jamaah, though leaning towards the Hanbali school of thought. In legal socialization, Salafi-Wahabi initiates it from the smallest social units to educational institutions and media, with a focus on study circles (halaqah). This legal socialization enhances legal awareness among the people of North Sumatra but also brings the potential for conflict and disharmony. Certain teachings within the Salafi-Wahabi manhaj, such as tabdi’, tadlil, tahzir, takfiri, and the restriction of learning exclusively from Salafi-Wahabi scholars, have the potential to create tension among groups and religious communities. While not all members of the Salafi-Wahabi manhaj share identical views, a majority tends to embrace these controversial concepts. Therefore, extremist ideologies emerging within the Salafi-Wahabi jihadist faction pose a potential threat to national political stability.